Methylation of 2-methylnaphthalene over metal-impregnated mesoporous MCM-41 for the synthesis of 2,6-triad dimethylnaphthalene isomers - Niftaliyeva, Aysel; Güleç, Fatih; Karaduman, Ali (Springer, 2020)
2,6-Dimethylnaphthalene (2,6-DMN) is one of the key intermediates for the production of polyethylene naphthalate (PEN), which demonstrates superior properties compared with the polyethylene terephthalate. However, the complex synthesis procedure of 2,6-DMN increases the production cost and decreases the commercialisation of PEN. In this study, selective synthesis of 2,6-triad DMN isomers (1,5-DMN, 1,6-DMN and 2,6-DMN) has been investigated by the methylation of 2-methylnaphthalene (2-MN) over mesoporous Cu/MCM-41 and Zr/MCM-41 zeolite catalysts. On the contrary of other DMN isomers, 2.6-triad isomers can effectively be converted to be profitable 2,6-DMN with an additional isomerisation reaction, which is a new approach to reach higher 2,6-DMN yield. The methylation reactions of 2-MN were investigated in a fixed-bed reactor at 400 °C and weight hourly space velocity of 1–3 h−1. The results showed that the activity of MCM-41 on the methylation of 2-MN has been enhanced with the impregnation of Cu. The conversion increased from about 17% to 35 wt% with the impregnation of Cu. Similarly, the 2,6-triad DMN selectivity and 2,6-/2,7-DMN ratio reached the maximum level (48 wt% and 1.95, respectively) over Cu-impregnated MCM-41 zeolite catalyst.
Keywords: Methylation; 2-Methylnaphthalene; 2,6-Dimethylnaphthalene; 2,6Triad DMN; MCM-41; PEN